2018
DOI: 10.1037/tep0000187
|View full text |Cite
|
Sign up to set email alerts
|

From advising to mentoring: Toward proactive mentoring in health service psychology doctoral training programs.

Abstract: Mentoring during graduate training confers a multitude of benefits. However, despite these benefits, health service psychology programs (e.g., counseling and clinical psychology) could benefit from additional attention to mentoring and associated outcomes. Although the field of health service psychology has examined advising during graduate training, we argue that mentoring is often distinct from advising and encourage a deliberate switch from the traditional role of faculty advisor to a more proactive role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 31 publications
0
41
0
Order By: Relevance
“…Informal and flexible mentoring has been considered a requisite as substantiated in several studies related to the workplace (Singh et al, 2002). Mentoring has also been considered as an integral part of training programs (Cobb et al, 2018) and traditional internships (Chao et al, 1992). As mentioned above, mentoring is a necessity in traditional as well as e-internships, and key roles of a mentor include clarifying communication, limiting ambiguity and reducing uncertainty (Jeske and Linehan, 2020).…”
Section: Review Of Literature and Hypotheses Developmentmentioning
confidence: 99%
“…Informal and flexible mentoring has been considered a requisite as substantiated in several studies related to the workplace (Singh et al, 2002). Mentoring has also been considered as an integral part of training programs (Cobb et al, 2018) and traditional internships (Chao et al, 1992). As mentioned above, mentoring is a necessity in traditional as well as e-internships, and key roles of a mentor include clarifying communication, limiting ambiguity and reducing uncertainty (Jeske and Linehan, 2020).…”
Section: Review Of Literature and Hypotheses Developmentmentioning
confidence: 99%
“…In the e-internship context mentoring can be a useful alternative approach due to its flexibility, and the option to keep interactions informal and need-focused. The merit of informal (as in more individually agreed and flexible) mentoring arrangements has been demonstrated in a number of studies in the workplace (Singh et al , 2002), training programs (Cobb et al , 2018) and traditional internships (Chao et al , 1992). The informal and thus predominantly flexible and relationship-based nature of these e-internships may be more conducive to developing increasingly natural and rewarding relationships (Jeske and Axtell, 2018a), particularly when the e-internships are of longer duration (e.g.…”
Section: Mentoring In E-internshipsmentioning
confidence: 99%
“…Broughton et al (2019) suggested that intentionality in mentoring practices includes purposeful and systematic engagement, particularly in areas of cultural competency and awareness. Mentoring practices that extend beyond advising are more a reflection of the department and institutional beliefs and actions in terms of commitment to direct engagement of empirical research, collaborative scholarly work and a more enhanced academic community (Cobb et al , 2018). In this study, intentionality is framed in the following two ways: intentional cultural awareness and training.…”
Section: Resultsmentioning
confidence: 99%